THE INFLUENCE OF INSTAGRAM SOCIAL MEDIA, TRUST, AND RISK ON INTEREST TO BUY ONLINE MAYOUTFIT PRODUCTS DURING COVID-19 - Taufiq Rachman; Dewi Putri Oktafiyanti (UPMI Management, 2022)
The coronavirus pandemic has had a major impact on changes in the economy and society in meeting their daily needs, not least what happened in the fashion world, such as Mayoutfit. The study examines the effect of Instagram social media on online buying interest. The study also examines the effect of trust on online buying interest and the effect of risk on online buying interest. The method used is quantitative because the data in the study are in the form of numbers, and the analysis uses statistics. The number of samples set is 100 respondents. Based on the results of the multiple regression test, it can be seen that the results of the t-test of the Instagram social media variable obtained a t-count value of 4.275 > t- table 1,984 and a significance of 0.000 < 0.05. The confidence variable obtained t arithmetic value of 1.124 < t-table 1.984 and a significance of 0.264 > 0.05. The value of tcount 6.424 obtained the risk variable> t-table 1984 and a significance of 0.000 < 0.05. then the results of F count 97.042 > F-table 2.70 and a significance value of 0.000 < 0.05. So it can be concluded that the Instagram social media variables and risk of Hₐ are accepted, and H₀ are rejected. Furthermore, the confidence variable H₀ is accepted, and Hₐ is rejected.